2022-RA-193-ESGO Cost-effectiveness of molecular profiling for endometrial neoplasia: a single institution experience. (20th October 2022) - Dheur, Adriane; Bours, Vincent; De Cuypere, Marjolein; Delbecque, Katty; Gennigens, Christine; Goffin, Frédéric; Gonne, Elodie; Hermesse, Johanne; Kridelka, Frédéric; Lovinfosse, Pierre; Pleyers, Clémence; Salmon, Alixe; et al.
Abstract : Introduction/Background: Endometrial cancer (EC) is the most common gynaecologic malignancy in developed countries. Hysterectomy remains the first-line treatment with pelvic lymph node staging being performed routinely. FIGO stage is central to define patients prognosis and their treatment planning. Molecular classification of EC includes 4 subtypes: POLE-ultramutated, mismatch-repair protein deficient (MMRd), p53-mutant and no specific molecular profile. Over the last three years, we have progressively implemented a detailed molecular screening for patients with EC and their risk stratification. Herein, we evaluate the global cost-effectiveness of this approach. Methodology: We conducted a monocentric retrospective study of 166 consecutive patients treated for EC at the University Hospital of Liège, between January 2019 and December 2021. Twenty-seven patients were excluded. Of the remaining 139, 87 patients had a complete immunochemistry and molecular biology for p53, MMR and POLE. Fifty were classified as low or intermediate risk, 15 as high-intermediate risk, 19 as high risk. Results: For these 87 patients, cost for complete analyses was €75, 820. FIGO stage defined high-risk patients four times more frequently than molecular biology; 8 patients were classified as high-risk due to FIGO stage III alone, 2 patients changed prognostic risk group from high-intermediate to high risk due to p53 mutation alone. However, the adjuvant treatment (external beam radiotherapy) decision was not modified due to the biomolecular profile. One patient with POLE-mutated EC was classified and treated as high-risk because of FIGO stage IIIC1. Conclusion: In our experience, molecular analysis changes the prognostic risk group in a limited number of cases and does not impact the final adjuvant treatment prescription. FIGO stage remains of primary importance in our treatment decisions. Had we performed p53 analysis by immunohistochemistry alone exclusively in low/intermediate-risk patients and microsatellite instability (MSI) testing only if patients were MMRd, €52, 777 would have been saved without theoretical oncological compromise.